1990
DOI: 10.1172/jci114534
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor-stimulated phosphoinositide hydrolysis in cultured rat inner medullary collecting tubule cells. Regulation by G protein, calcium, and protein kinase C.

Abstract: Epidermal growth factor (EGF) exhibits specific saturable binding to cultured rat inner medullary collecting tubule cells and stimulates inositol trisphosphate (IP3) production by these cells in a dose-dependent fashion. EGF-stimulated IP3 production is enhanced by GTP-ys or AJF4 and is inhibited by GDPBs or pertussis toxin. Alterations in extracellular Ca2" have no effect on either basal or EGF-stimulated IP3 production. Similarly, treatment with EGTA which decreases cytosolic Ca" is without effect. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The concentration dependence for hEGF-stimulated Ins-P3 production in isolated membranes illustrated in Fig. 1 is similar to that shown by Teitelbaum et al ( 12), who reported a significant increase of Ins-P3 production upon addition of 10-8 M or higher concentrations of EGF to cultured rat inner medullary collecting tubule cells (12 changed for 2 h of incubation in the absence of added peptide (2). Addition of hEGF to suspensions of collecting ducts resulted in a concentration-dependent production of IGF I (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The concentration dependence for hEGF-stimulated Ins-P3 production in isolated membranes illustrated in Fig. 1 is similar to that shown by Teitelbaum et al ( 12), who reported a significant increase of Ins-P3 production upon addition of 10-8 M or higher concentrations of EGF to cultured rat inner medullary collecting tubule cells (12 changed for 2 h of incubation in the absence of added peptide (2). Addition of hEGF to suspensions of collecting ducts resulted in a concentration-dependent production of IGF I (Fig.…”
Section: Resultssupporting
confidence: 87%
“…One mechanism by which EGF transmits its "signal" across the plasma membrane of renal collecting duct cells is via activation of phospholipase C (12). To establish that the potential exists for EGF signal transduction across the plasma membrane of isolated rat renal collecting duct cells, membranes prepared from collecting duct segments were incubated for 15 s in the absence of added peptide or in the presence of 10-10, 10-8, or 10-6 M hEGF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though studies on the cultured normal rat IMCD do not support inhibition of AVP-stimulated cAMP generation by PGE2 (28), we considered the possibility that excess PG production may be responsible for the lack of AVP-responsiveness in CRF. Therefore, we examined the response of CRF cells to AVP in the background of cyclooxygenase inhibition with 5 uM flurbiprofen which we have previously shown to decrease ionophore-stimulated PGE2 production by > 97% (29). However, as seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Abbreviations used in this paper: AC, adenylyl cyclase; DAG, diacylglycerol; DOG, dioctanoylglycerol; EGF, epidermal growth factor; H7, 1-(5-isoquinolinylsulfonyl).2-methylpiperazine; H8, N-[2-methylamino)ethyl]-5-isoquinoline-sulfonamide; IPI, inositol monophosphate; IP2, inositol bisphosphate; IP3, inositol trisphosphate; PLA2, phospholipase A2; PLC, phospholipase C; RIMCT, rat inner medullary collecting tubule. ble for mediating the enhanced hydraulic conductivity of the apical membrane. Recent studies from this laboratory have demonstrated that in addition to AC activity, cultured inner medullary collecting duct cells also exhibit hormonal stimulation of phospholipase C (PLC) activity upon exposure to epidermal growth factor (EGF) (1).…”
Section: Introductionmentioning
confidence: 99%